Carbonate ooids of the Mesoarchaean Pongola Supergroup, South Africa. Issue 6 (24th July 2017) - Siahi, M.; Hofmann, A.; Master, S.; Mueller, C.W.; Gerdes, A.
Abstract: Ooids from the Mesoarchaean Chobeni Formation, Pongola Supergroup, KwaZulu‐Natal, South Africa are older than any ooids reported to date. They are made of dolomite and ankerite and show concentric, radial‐concentric, micritic, and radial fabrics. Radial ooids are interpreted to have originated from high‐Mg‐calcite and probably formed by microbial activity in a low‐energy regime, while concentric ooids had an aragonite precursor and formed biotically under agitated/high‐energy environmental conditions. Micritic ooids formed via the recrystallization of concentric ooids. Ooids and other allochems, such as intraclasts and peloids, contain carbonaceous matter. The close association of carbonaceous matter within ooid cortices with metabolically important elements, such as N, S and P, as identified by nano‐scale secondary ion mass spectrometry analysis, allows us to propose a biologically induced origin for some ooids. By analogy with modern examples, a variety of microbial communities probably played a role in carbonate precipitation and ooid formation. Shale‐normalized rare earth element (REE) distribution patterns of ooids and other allochems show positive LaSN, GdSN and YSN anomalies, superchondritic Y/Ho ratios and depleted light rare earth elements (LREEs) relative to the heavy rare earth elements (HREEs), which resemble those of seawater. These anomalies are less pronounced than expected for an open marine setting, which is interpreted as evidence for deposition in restricted shallow marine environments. Non‐seawater REE patterns in recrystallized matrix and pore‐ and vein‐filling carbonate likely reflect redistribution of rare earth elements during post‐depositional alteration and/or reflect differences in the elemental and REE compositions of diagenetic fluids.